Optimizing the Voice of Customer (VoC) Strategy through Agentic AI-Based Quality Control System - Meilina, Restin; Santoso, Rachmad; Anam Al Manshur, Moh Syaiful (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
In today’s customer-driven industrial landscape, the ability of companies to align product quality with evolving customer expectations has become a critical success factor. This study proposes an integrative model that incorporates Voice of Customer (VoC) into a Quality Control (QC) system powered by Agentic Artificial Intelligence (AI). The system is designed to autonomously analyze customer feedback, adjust quality parameters, and execute improvements within the production process without human intervention. Using a quantitative approach, the study evaluates the effectiveness of the system through key strategic indicators such as customer satisfaction, cost efficiency, and marketing performance. The findings reveal that implementing Agentic AI in QC not only enhances product quality but also transforms QC into a data-driven marketing tool that is both proactive and adaptive. This model aligns with the vision of Industry 5.0, where technology and human-centric needs converge to enable continuous and intelligent quality improvement.